Perselingkuhan dan Relasi Sosial Modern: Tindakan Preventif dalam Tafsir Ibnu Katsir dan Hadis “Ipar Adalah Maut” - Sefri Auliya; Hidayatul Azizah Azizah Gazali; Afzico Muhammad Chandra; Desri Nengsih; Winda Meri Susila (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
The transformation of social relations in the digital era has reshaped patterns of interaction between men and women, increasing opportunities for infidelity through both direct and digital communication. This study aims to examine Islamic preventive measures against infidelity based on Ibn Kathīr’s interpretation of Qur'an Surah An-Nūr (24):31 and the prophetic tradition (ḥadīth) al-ḥamwu al-mawt (